THE LATIHAN SENAM AEROBIK MENINGKATKAN KUALITAS TIDUR PADA MAHASISWI PROGRAM STUDI FISIOTERAPI FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Malini, Made Meita; Silakarma, IGN Dedi; Sundari, Luh Putu Ratna (Majalah Ilmiah Fisioterapi Indonesia; Vol 3 No 2 (2015): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2015.v03.i02.p01)
Daily habits and activities of students may affect their quality of sleep. The purpose of this study is to know whether aerobic exercise can improve sleep quality for female students. The method of this study is pre experimental which used one group pre-test and post-test design. Nineteen students of physiotherapy had volunteered in this study, they were at the age of 18-21 (mean 19,68 ± 1,06) years old. Participants joined to do aerobic exercise for 6 weeks which was 3 times a week and 60 minutes duration for each exercise. Measurement of sleep quality used the Pittsburgh Sleep Quality Index (PSQI) before exercise and 6 weeks after doing the exercises. The result of this study was the average of global score before exercise was 7,89 (SD ± 1,82) and the mean value after 6 weeks of exercise was 3,89 (SD ± 1,79). Statistical analysis of the data used non-parametric wilcoxon test, the result was (p=0,001). It can be concluded that the global score decrease before and after aerobic exercise, which means an increase in the quality of sleep on the female students after doing aerobic exercise for 6 weeks.
Keywords: sleep quality, female student, exercise, aerobic dance.